Dynamic analysis of a mechanical press equipped with a half–toroidal continuously variable transmission. (14th January 2015) - Yildiz, A.; Kopmaz, O.
This paper proposes a novel mechanical press concept that consists of a half–toroidal continuously variable transmission (CVT) to obtain more speed flexibility than the classical one. In this way, one can achieve a quite wider range of speed variation, e.g., from 0.5 to 2, which cannot be provided efficiently by using other methods such as electrical inverter technique. Moreover, using this new design concept enables us to increase the crankshaft speed beyond the one achieved from the nominal speed of the motor. This feature is not feasible in classical mechanical presses. Thus, the different manufacturing processes such as cutting, bending, punching, to some extent deep drawing can be operated by the same press without any change in the system components. For analysing the dynamics of this new system, a theoretical model is established by combining the equations of motion of classical mechanical press and CVT. The speed fluctuations of crank shaft are investigated under the different CVT ratios. The results of simulations indicate that adding a CVT to a mechanical press is feasible in all conditions provided that an additional flywheel is added to the system.